2022
DOI: 10.1097/mjt.0000000000001496
|View full text |Cite
|
Sign up to set email alerts
|

Fluvoxamine in Nonhospitalized Patients With Acute COVID-19 Infection and the Lack of Efficacy in Reducing Rates of Hospitalization, Mechanical Ventilation, and Mortality in Placebo-Controlled Trials: A Systematic Review and Meta-Analysis

Abstract: Background: Recent clinical trials have investigated the use of fluvoxamine in preventing clinical deterioration in nonhospitalized patients with acute COVID-19 infection via stimulation of sigma-1 receptors, which regulates cytokine production and functional inhibition of acid sphingomyelinase activity, which may prevent infection of epithelial cells with SARS-CoV-2. However, the role of fluvoxamine is currently unclear because of a paucity of studies, particularly because the drug is being repurposed as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…This study has limitation. From the results of several meta-analyses, there is an ongoing debate over the beneficial effects of fluvoxamine for COVID-19 [96][97][98][99][100][101][102][103]. A recent meta-analysis using 6 randomized clinical trials and 5 observational studies demonstrated that the medium dose (100 mg twice daily) of fluvoxamine, but not low dose (50 mg twice daily), was associated with a 21% reduction in the risk of hospitalization, and a 28% reduction in the risk of mortality [104].…”
Section: Limitationmentioning
confidence: 99%
“…This study has limitation. From the results of several meta-analyses, there is an ongoing debate over the beneficial effects of fluvoxamine for COVID-19 [96][97][98][99][100][101][102][103]. A recent meta-analysis using 6 randomized clinical trials and 5 observational studies demonstrated that the medium dose (100 mg twice daily) of fluvoxamine, but not low dose (50 mg twice daily), was associated with a 21% reduction in the risk of hospitalization, and a 28% reduction in the risk of mortality [104].…”
Section: Limitationmentioning
confidence: 99%
“…Additionally, a recent systematic review and meta‐analysis published by Bhuta et al 82 have not indicated the beneficial effects of fluvoxamine in nonhospitalized COVID‐19‐positive patients versus a COVID‐19‐positive placebo group (a total of 1762 patients were included, 886 received fluvoxamine and 876 patients received placebo). Overall, the results showed little to no difference between the rates of hospitalization, mechanical ventilation, and mortality between the fluvoxamine versus the placebo group 82 …”
Section: Contestation Of Antidepressant and Fiasmas Use Against Sars‐...mentioning
confidence: 99%
“…However, most of the developed world took an opposite approach, by focusing on COVID-19 specific pharmaceuticals. Honduras lacked the financial means to implement or manufacture novel drugs, thus, compelling the use of the best available evidence in that moment, even when opposing results emerged ( Bhuta et al, 2022 ; Ontai et al, 2022 ; Valerio Pascua et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%